Predicting The Mental Health of Teachers Based on The Variables of Self-Efficacy andSocial Support - Sadegh Nabavi; Faramarz Sohrabi; Golamali Afrouz; Ali Delavar; Simin Hosseinian (Iranian Association of Health Education and Health Promotion, 2017)
Background and Objective: Self-efficacy and social support is a effective factors in mental health, And to help them cope with stressful situations and anxiety, and trauma they experienced fewer. The main objective of this study was to investigate the relationship between self-efficacy, and social support and prediction of mental health among teachers is based on these variables.. Methods: Due to the nature and objectives of the research, research design is non-experimental and correlation. The study population consisted of all elementary and secondary school teachers has been Tehran city. 447 teachers with cluster random sampling were selected for this study. In order to collect research data from the General Health Questionnaire (28- GHQ), general self-efficacy questionnaire Sherer & colleagues Social Support Questionnaire Wax and colleagues use was performed. for analysis of data with descriptive and inferential statistics (multivariate regression)was used. Results: The results showed that self-efficacy and social support, there is a significant negative correlation with physical symptoms. Therefore, self-efficacy and social support can change physical symptoms among teachers significantly(P<0/‎001‎) explain and predict. Between self-efficacy and social support, there is a significant negative correlation with anxiety and insomnia. So they can make changes related to anxiety and insomnia among teachers significantly(P<0/001) explain and predict. Between self-efficacy and social support, social dysfunction there is a significant negative relationship. But just changing social dysfunction among teachers' self-efficacy could significantly (P˂0/05) to explain and predict. Significant negative relationship between self-efficacy and social support with depression there. So those two variables can change significantly among teachers depression (P˂0/001) to explain and predict. Conclusion: it can be concluded that using the ways to increase self-efficacy of teachers in teacher training, to provide social support and promote their socio-economic situation in the course of employment can be helped to improve their mental health among them.